POST-PROSPECTING RADIOECOLOGICAL SURVEYS ON THE TOMTORSKOYE RARE METAL DEPOSIT (SAKHA REPUBLIC (YAKUTIA)) - V. V. Kasatkin; A. V. Kasatkin; V. A. Ilyichev; N. S. Sedov; E. M. Vasilenko; S. V. Evdokimov (Радиационная гигиена)
In 2017, the specialists of the radiation safety laboratory of JSC «VNIPIpromtekhnologii» conducted a radioecological examination of the «Buranny», «Severny» and «Yuzhny» sites in the Tomtorskoe rare metal deposit (the northern part of the Olenek ulus of the Sakha Republic (Yakutia)). By this time, exploration work was completed at the field with an assessment of the radiation situation. Due to the fact that the amount of information received was not sufficient for a comprehensive analysis and prediction of the radiation situation, it was decided to conduct an additional radioecological survey at the field and in the adjacent area. The research program included field and laboratory work: gamma surveying of the territory, measuring the flux density of alpha and beta particles, gamma spectrometric measurements, environmental sampling, residues of drill cuttings and core, conducting research on the content of natural and man-made radionuclides, as well as individual chemical elements in the selected samples. According to the results of the research, a conclusion was drawn about the normal radiation situation in general in the field. Certain sites of the radioactive contamination was associated with an anthropogenic impact on the ecology of the field during exploratory drilling with the extraction of core from the ore body to the surface of the sites.